Considerations for racial differences in the athlete's heart and related cardiovascular disease - Lewis, J. F. (Cardiology Clinics, 1997)
Athletic training is often associated with modest increases in left ventricular chamber size, wall thickness, and mass, which appear to be related to the level and intensity of training as well as the type of activity performed. It appears that for given levels and types of training, some individuals show more marked morphologic changes. It has been speculated that the cardiac alterations that occur with athletic conditioning may be due, in part, to genetic factors that exist independent of training. Related to this issue is the possibility that racial (or biologic) differences in cardiac response to exercise may also exist. This article reviews the available data that address racial differences in the cardiac response to exercise and to left ventricular pressure overload and the implications of these findings.